2002
DOI: 10.1038/sj.jea.7500206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ambient air concentrations of polycyclic aromatic hydrocarbons in Germany from 1990 to 1998

Abstract: All available polycyclic aromatic hydrocarbon ( PAH ) concentration data in ambient air obtained over the past 10 years in Germany were evaluated to clarify whether it is justified to use benzo( a )pyrene ( BaP ) as a marker compound for the total PAH exposure. The data basis comprises annual mean concentrations from 1990 to 1998 supplied by the emission protection authorities of the federal states with additional information on the region, year and site of measurement. The data are very heterogeneous with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In our study, DBA concentrations ranged from 0.02 to 0.95 ng/m 3 (median 0.20 ng/m 3 ), which is similar to the measured values observed in 1996 in the nearest village, Waldenbuch, in earlier studies (Marbach and Baumbach 1998) and comparatively higher than the values reported for rural areas (median 0.11 ng/m 3 ) of Germany during 1990–1998 (Fertmann et al 2002). They are, however, lower than that reported for Kurkimäki, Finland (mean 0.4 ng/m 3 ) during the winter of 2006 (Hellen et al 2008).…”
Section: Resultssupporting
confidence: 90%
“…In our study, DBA concentrations ranged from 0.02 to 0.95 ng/m 3 (median 0.20 ng/m 3 ), which is similar to the measured values observed in 1996 in the nearest village, Waldenbuch, in earlier studies (Marbach and Baumbach 1998) and comparatively higher than the values reported for rural areas (median 0.11 ng/m 3 ) of Germany during 1990–1998 (Fertmann et al 2002). They are, however, lower than that reported for Kurkimäki, Finland (mean 0.4 ng/m 3 ) during the winter of 2006 (Hellen et al 2008).…”
Section: Resultssupporting
confidence: 90%
“…There were 145 women with missing values for the resulting ambient BaP estimate. BaP was used as a proxy for total PAH exposure, since BaP is an accurate indicator of PAH exposure and carcinogenicity (Fertmann et al, 2002).…”
Section: Ambient Bap Estimate (Model C)mentioning
confidence: 99%
“…In particular, the abundance of BaP was reduced by 95%. A significant decrease of BaP was observed in air samples collected in the North Rhine Westphalia area: the median concentration was 1.6 ng m -3 in 1991 and 0.7 ngm -3 in 1997 (Fertmann, Tesseraux et al, 2002) Airborne PAHs, monitored regularly at rooftop height from 1991 to 1998 in London and Manchester (UK), exhibited a clear decreasing trend at both sites: 4.1 years was the half-life calculated for BaP (Prevedouros, Brorstrom-Lunden et al, 2004). More recently, another study updated to 2005 the PAH concentrations found in six UK locations (Meijer, Sweetman et al, 2008 (Menichini, Belladonna et al, 2006) showed a generalized decreasing trend in the last few years.…”
Section: Discussion On Bap Trends Found In Genoamentioning
confidence: 94%
“…Possible explanations for the short time observed decline of PAH concentrations in European countries were seasonal factors as photo degradation (Schauer, Niessner et al, 2003), different contamination of air masses impacting monitored sites, specific local emissions, i.e. domestic heating (Prevedouros, Brorstrom-Lunden et al, 2004) and industrial activities (Fertmann, Tesseraux et al, 2002). Regulations designed to reduce emissions from mobile sources were identified as possible explanation for long time PAH pollution trends (Menichini, Belladonna et al, 2006), but no clear demonstration was offered by authors for these hypotheses.…”
Section: Trends Of Pah Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation